A Discourse of the Female Body in an Ancient Sundanese Literary Work of Lutung Kasarung: An Eco-Feminist Approach - Isnendes, Retty; Haerudin, Dingding (TAWARIKH, 2011)
ABSTRACT: This research investigates Sundanese narrative poems in âLutung Kasarungâ (LK) with an eco-feminist theory. This research draws upon an analytical descriptive method of literary research with a data collection method and a feminist text analysis. The data sources were two texts of narrative poems of LK which had been converted into a story by Ahmad Bakri (1976) and documents from an oral story which had been rewritten by C.M. Pleyte (1910). This study reveals that: (1) there was an event that underlied the representation of the female body, there was a discourse that explored the female body, and the characters presented were related and formed an event in the social reality of the Kingdom of Pasirbatang; (2) a denial of Carolyn Merchantâs theory, particularly in the context of women and ecology as well as as of women and reproduction. The denial was represented by the character of Purba Rarang; and (3) there was injustice towards female characters, although it was hidden beneath the writerâs worship to women.KEY WORDS: Eco-feminist, a discourse of the female body, poem of âLutung Kasarungâ, and Sundanese society.Â Â About the Authors: Retty Isnendes, M.Hum. and Dr. Dingding Haerudin are Lecturers at the Faculty of Language and Arts Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. They can be reached at: chyerettyisnendes@gmail.com and dingdinghaerudin@yahoo.co.idHow to cite this article? Isnendes, Retty & Dingding Haerudin. (2011). âA Discourse of the Female Body in an Ancient Sundanese Literary Work of Lutung Kasarung: An Eco-Feminist Approachâ in TAWARIKH: International Journal for Historical Studies, Vol.3(1) October, pp.109-120. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 14, 2011); Revised (September 17, 2011); and Published (October 28, 2011).